Agama dalam Negara: Politik Islam Indonesia Kontemporer - M. Sidi Ritaudin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2009)
All of religion in Indonesia have got such guarantee of existence, according to Constitution of 1945. In its preamble was laid dawn that “With the blessing and mercy of Allah the Almighty and urge by the noble desire for a national life of independence, the Indonesian people hereby proclaim their independence”. This sentence expresses the feelings of gratitude towards Allah the Almighty. This expression represents obviously the manifestation of faith in accordance with the religious teaching. The position of religion has been made clear, based on article 29 of the 1945 Constitution, that the state of Indonesia is based on the Believe in the One Supreme God. This article, declare clearly that the State guarantees freedom for every citizen to adhere to his religion and to perform his religious duties. Accordingly, the Government will endeavor to create condition which will promote harmoniously life among people of different religion, in its ultimately effort to strengthen national unity.